(untitled) (The Pakistan Development Review, 1986)
The question that I have set out to answer in today’s presentation is a valueladen one, since I plan to give you my perception of how adequately (or inadequately) the roles of women are changing in Pakistan. My conclusions are, however, based on an objective and scientific evaluation of the existing data. With regard to data, I do not need to belabour the subject of the shortage of data or the dearth of good quality data before an audience like the present one. The shortages and weaknesses of demographic and socio-economic data are all too well known to you. I will therefore go directly to setting out the organization of my presentation. I will begin with a brief discussion of the terms of reference which have guided my analysis. This is followed by an investigation of the quantifiable changes in the roles of women. The time period covered under this section falls generally between 1951 and 1981, owing mainly to the availability of census data for these years. In the third section I will focus on the adequacy of changes in relation to national targets, as well as the international experience on the various indicators of change. In the final section, I will discuss the issues and complexities involved in bringing about changes in the existing roles and role definitions.